Roles of tourism in the local people’s opinion regarding human-macaque conflict in the central High Atlas, Morocco - Abderrazak El Alami; Abderrahman Chait (Revue de Primatologie)
Conflict between local people and wild macaques is one of the greatest challenges to Macaca sylvanus conservation in Morocco. The objective of this study was to assess the human-Barbary macaque interaction in a tourist and a non-tourist sites in the central High Atlas Mountains of Morocco. From February 2004 to December 2009, we collected data on local people’s opinions about the advantages and disadvantages of Barbary macaque’s presence. Results showed that in the tourist site, the percent of interviewees who confirm the macaque’s presence and who recognize the picture of the local monkey are significantly higher than in the non-tourist site. Barbary macaques are viewed favorably in the tourist site for their benefits to tourism. On the contrary, they are viewed unfavorably in the non-tourist site and this is mainly due to crops raiding and the competition with livestock for food resources. Conservation efforts on behalf of this specie should consider the local people’s opinion regarding human-macaque conflict and the advantages and disadvantages of tourist activities.